KAUSATIF DALAM BAHASA INDONESIA DAN BAHASA INGGRIS: SEBUAH TELAAH TIPOLOGIS - Susi Herti Afriani (Fakultas Adab dan Humaniora UIN Raden Fatah, 2016)
This research is aimed at describing causative construction in Indonesian and English, by choosing the same verb, and followed by comparing them. Causative construction in Indonesian and English found in three level, they are: first, lexical causative construction, the Indonesian as well as English will create cause-effect construction, which is formed in a lexical unit (Y). The relation of formality is seen in semantic relation, for the reason, a form of lexical causative construction can be seen from the meaning and it’s single verb. Second, in the Indonesian morphology causative construction, “effect” typically is signed by a verb (Y), for instance, the word mati “dead” in mematikan “to cause a dead”, (causation). It is indicated by an affix (Z) in-’kan’. The formality separation is related to a raising of separation between cause-effect concept, while English has not put address on a construction of morphology causative. Third, in the construction of periphrastis causative construction (analytical) ‘cause’ and ‘effect’ is expressed by a separated verb, and also it has a large formality division, between ‘cause’ ‘sebab’ and ‘result’ ‘hasil’. Both of Indonesian and English have put address on this construction. In all three construction analysis above, it is clearly seen that there is a correlation between causative type and causation in the iconicity pyramid, which stated by Haiman.